Communication in health work during the COVID-19 pandemic - Maria Eunice Nogueira Galeno Rodrigues; Adriano da Costa Belarmino; Lívia Lopes Custódio; Ilvana Lima Verde Gomes; Antonio Rodrigues Ferreira Júnior (Universidad de Antioquia, 2020)
Objective. Report on communication and qualified listening in nursing work in the face of the COVID-19 pandemic. Methods. This descriptive, theoretical and reflexive report was developed by nurses between March 20th and May 25th 2020 at Emergency Care Services in the city of Fortaleza, Ceará, Brazil. Health communication served as the theoretical background for this research. Results. Two main thematic categories were highlighted: (i) Resignifications of communication in the work relationships of the health team and (ii) Guided listening to users by nurses at the Emergency Care Services during the pandemic. Conclusion. The experience revealed an excerpt of what is found under the conditions of the current situation resulting from COVID-19. Communication turned into an essential tool to maintain professional relationships and culminate in collaboration and cooperation of the team in order to provide a close relationship with the user and promote the quality of health care processes.